The Effect of Lengthening Job Tenure on Managers' Organizational Commitment and Turnover - Taylor, M. Susan; Audia, Giuseppe; Gupta, Anil K. (Organization Science, 1996)
Using the psychological contract literature as a framework, we examined upwardly mobile managers' reactions to lengthening job tenure brought about by slower organizational growth and greater competition among peers. We hypothesized that managers tend to view lengthening job tenure as a violation of the relational employment contract held with their corporate employers and, therefore, experience decreased organizational commitment, and an increased probability of turnover. We also examined three variables expected to exacerbate or to offset these relationships: manager's past career success, their current level of job responsibility, and the candidness of the career feedback they received from the organization. The sample consisted of 109 general managers working in Fortune 500 companies. Results showed that lengthening job tenure decreased managers' affective commitment and increased the likelihood of turnover during a three year follow-up period for managers who had previously experienced greater success in the organization and for those whose jobs included higher levels of responsibility. Contrary to hypotheses, candid career feedback did not offset the negative effects of lengthening job tenure on the dependent variables. Conceptual and practical implications are discussed.